Peningkatan Pengetahuan Kader Kesehatan Terhadap Hipertensi - Aisyiah, Intan Kamala; Adhyka, Nurmanines; Mindayani, Sri; Arief, Amrizal; Yulianita, Yulianita (Universitas Gajah Putih, Indonesia, 2023)
Hypertension can cause degenerative diseases, and when it worths, death. It’s called silent killer because it can attack anyone with no specific signs. Based on several studies, people who suffer from hypertension are 12 times more likely to have a stroke and 6 times more likely to have a heart attack. This aim of community service methods used are lectures and discussions. The participants who attended this activity were 28 health cadres, lecturers and public health students at Baiturrahmah University. This activity took place on March 10, 2022. In this activity an assessment of cadres' knowledge about hypertension was carried out before and after being enlightenment. The average knowledge of cadres about hypertension before the activity was 5.10 while after the counseling was 7.14. From this activity it shows that there are differences and an increase in the knowledge of health cadres after counseling with a P Value 0.00. It is suggested to the public health service that it is necessary to routinely increase the knowledge of cadres about hypertension with various health promotion methods